2018
DOI: 10.1016/j.yebeh.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GAD antibodies in a cohort of neuropsychiatric patients

Abstract: Antiglutamate decarboxylase (anti-GAD) antibodies relate to epilepsy with or without cognitive complaints. However, psychiatric symptoms were almost absent in anti-GAD positive patients, and the presence of anti-GAD antibodies contributed little to the prognosis in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
12
0
5
Order By: Relevance
“…Case-series in TIDM also reported an association between the GAD epitope pattern and the occurrence of epilepsy [67,68]. One recent case-control study indicated that TIDM was more likely in people with epilepsy who were anti-GAD positive compared to those who were negative [69].…”
Section: Type 1 Diabetes Mellitus (Tidm)mentioning
confidence: 97%
“…Case-series in TIDM also reported an association between the GAD epitope pattern and the occurrence of epilepsy [67,68]. One recent case-control study indicated that TIDM was more likely in people with epilepsy who were anti-GAD positive compared to those who were negative [69].…”
Section: Type 1 Diabetes Mellitus (Tidm)mentioning
confidence: 97%
“…Here, we report on a large consecutive series of patients newly referred to a large Epilepsy Center over more than three years suffering from temporal lobe adult-onset seizures (TAOS) with clinical findings suggestive of an autoimmune origin. Compared to previous studies on ABs in highly selected epilepsy patient cohorts [20][21][22][23], here, we have assessed for the first time the clinical results in a patient group, in which the presence of autoABs is suspected but has not been identified yet, and compared this group to patients positive for 'neuroABs'.…”
Section: Introductionmentioning
confidence: 99%
“…In our series, orofacial dyskinesia was noted in 7/11 cases. 5 Journal of Immunology Research AE with anti-GAD65 antibodies is a rare condition in children, and to the best of our knowledge, only 16 pediatric cases were reported [11][12][13][14][15]. It is characterized by limbic involvement with refractory seizures, cognitive impairment, and behavioral disturbances [16].…”
mentioning
confidence: 99%